The emergence of Asian intellectuals - Mojares, Resil B. (Asian Studies, 2013)
The paper takes a look at how a self-conscious community of Asian intellectuals came to be formed at the turn of the twentieth century, inspired by such factors as the rise of Japan as a world power and the advance of anti-colonial movements in various parts of Asia. It takes as an example the case of the Philippines where a sense of the ‘region’ was an ntegral part of the Filipino nationalist movement in the late nineteenth-century. In particular, the paper looks at the case of Mariano Ponce (1863–1918), who may well be called “the first Filipino Asianist. ”In recounting his story, the paper underscores the importance of local histories of Asianism as a corrective to the tendency to locate in the West the beginnings of area studies.